2008
DOI: 10.1192/bjp.bp.107.041723
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 5-HT2Creceptor and leptin gene polymorphisms, smoking and drug treatment on metabolic disturbances in patients with schizophrenia

Abstract: The findings suggest interacting genetic risk factors and smoking influence development of metabolic syndrome in patients on antipsychotic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 20 publications
(34 reference statements)
4
58
0
3
Order By: Relevance
“…This could implicate that both polymorphisms have a different effect on receptor functioning or a different interaction with other metabolicregulating systems. One of the explanations could be a different interaction with the leptine system as reported by Templeman et al, 19 Yevtushenko et al, 24 and Gregoor et al…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…This could implicate that both polymorphisms have a different effect on receptor functioning or a different interaction with other metabolicregulating systems. One of the explanations could be a different interaction with the leptine system as reported by Templeman et al, 19 Yevtushenko et al, 24 and Gregoor et al…”
mentioning
confidence: 89%
“…This was unexpected as the 759 C/T polymorphism has been repeatedly associated with antipsychotic-induced weight gain, and weight gain is an important predictor for meeting the criteria for the metabolic syndrome. 12,[16][17][18][19][20][21][22][23][24] The fact that this is the third study in which we found an association between prevalence of the metabolic syndrome and HTR2C rs1414334 genotype, but not 759C/T genotype, requires an explanation. We suggest that we are dealing with two different phenotypes in two different phases of the disease with weight gain at the initiation of treatment and the presence (and prevalence) of the metabolic syndrome, after a longer period of treatment with antipsychotic drugs.…”
mentioning
confidence: 94%
“…Many people with psychotic illness have a rather sedentary lifestyle (Daumit et al, 2005) and take less exercise than the general population (Osborne et al, 2007b). The higher prevalence of smoking in people with schizophrenia, even in the early stages of the illness (Barnes et al, 2006), appears to have no protective effect on body weight and has been reported to be associated with increased liability to metabolic syndrome (Yevtushenko et al, 2008).…”
Section: Factors Driving Metabolic and Cardiovascular Risk In Psychosismentioning
confidence: 99%
“…This is also seen in the UK population. A Northern Ireland study of people with schizophrenia showed a high prevalence of obesity (40%) and metabolic syndrome (38%) (Yevtushenko et al, 2008).…”
Section: Factors Driving Metabolic and Cardiovascular Risk In Psychosismentioning
confidence: 99%
“…5-hydroxytryptamine receptor 2C; Xq23). Istraživanje SNP-ova u genu HTR2C posebice opravdava činjenica da pojedini antipsihotični lijekovi, poput klozapina i olanzapina, koji pokazuju visok afinitet za navedeni receptor, zapravo najviše pridonose razvoju metaboličkih abnormalnosti u pacijenata sa shizofrenijom 19,[134][135][136][137] . Nadalje, u novije se vrijeme značaj pripisuje i genima koji sudjeluju u kontroli energetskog metabolizma, kao što su LEP (engl.…”
Section: Genetika Metaboličkog Sindroma U Shizofrenijiunclassified